SUN-579 Fetal Thyrotoxicosis: Maternal Graves’ Disease Leading to Fetal Hyperthyroidism - Spoke, Christopher (J Endocr Soc, 2019)
Case Description: We present a 27-year-old female with history of Graves’ Disease and post ablative hypothyroidism. She established care in the endocrinology clinic at 17 weeks gestation after screening ultrasound demonstrated fetal goiter and fetal tachycardia. Her labs were significant for Thyrotropin receptor antibody >40.0 (0.00 - 1.75 IU/L). She was transitioned to levothyroxine monotherapy for treatment of her post-ablative hypothyroidism. Methimazole and metoprolol were initiated for treatment of fetal hyperthyroidism. Despite initiation and titration of methimazole, repeat ultrasounds showed increasing fetal goiter. Cordocentesis was pursued at 22 weeks gestation to further guide thioamide therapy. Discussion: Fetal hyperthyroidism is a rare complication of maternal Graves’ Disease, usually presenting at or after 20 weeks gestation. Our patient began to exhibit signs of fetal thyrotoxicosis at 16 weeks gestation. Assessment of fetal response to thioamide therapy relies on fetal heart rate and sometimes cordocentesis, which raises uncertainty in management. Thioamide therapy should be titrated every 1-2 weeks with fetal goal heart rate of 140 beats/min. Serial fetal ultrasounds to assess fetal heart rate, amniotic fluid, and goiter size are recommended to assess for response to treatment. Cordocentesis is considered when fetal thyroid status is uncertain. We present our clinical experience, current recommendations along with recent developments in the field. References:1. De Groot, Leslie, et al. "Management of thyroid dysfunction during pregnancy and postpartum: an Endocrine Society clinical practice guideline." The Journal of Clinical Endocrinology & Metabolism 97.8 (2012): 2543-2565.